The Anatomy Of Radical Islamism In Contemporary Indonesia: Towards A More Workable Deradicalization Project - Masdar Hilmy; Alimuddin . (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2019)
This article seeks to provide a general overview of the picture of radical Islamism in contemporary Indonesia and relates it with the a more workable deradicalization project. The wrong measures taken by the authority in countering radicalism is due mainly to the fact that most of them understood the complex reality of radical Islamism from single monolithic approach wrong. The anatomy of radical Islamism forms two major parts; flesh-and-blood (soft-ware or ideology of radicalism as the spirit) and skeleton (as the hard-ware of radicalism). Based on such an anatomy, the deradicalization must be carried out in two major ways; soft approach and hard-approach. The soft approach of deradicalization must address two things as follows; 1). Mainstreaming religious moderation and; 2). Creating structural equilibrium in Muslims’ life.